Immune response to rabies post-exposure prophylaxis in patients with non-HIV secondary immunodeficiencies. Issue 33 (14th July 2020) - Parize, Perrine; Poujol, Philippe; Morineau Le Houssine, Pascale; Goesch, Julia; Lucet, Cora; Basuyau, Laura; Cailhol, Johann; Dacheux, Laurent; Bourhy, Hervé; Consigny, Paul-Henri
Highlights: Rabies vaccine response may be altered in immunocompromissed (IC) individuals. The immunigenicity of rabies PEP was assessed in IC patients. An inadequate response was documenetd in 6/28 patients using ELISA. Inadequate response was unpredictable and not explained by the variables studied. This study supports the systematic assessment of post-PEP response in IC patients. Abstract: Background: This study sought to determine the proportion of individuals with non-HIV secondary immunodeficiencies presenting inadequate antibody titers after rabies post-exposure prophylaxis (PEP) and to identify variables associated with inadequate response. Methods: A retrospective review of the records of immunocompromised patients having received a full course of PEP after a rabies exposure and having been tested for post-PPE antibody titers in two French Antirabies Clinics, between 2013 and 2018, was conducted. Antibody titers < 0.5 EU/ml (ELISA) were classified as inadequate. Results: A total of 28 individuals were included, 6 had inadequate post-PPE titers. None of the tested variable was independently associated with inadequate titers. Conclusions: Inadequate response was unpredictable and not explained either by the characteristics of patients or by the PEP regimen they received. These findings support the WHO recommendation to systematically assess post-PEP response in immunocompromised patients to detect non-responders, who might require an additional dose.